PERTUMBUHAN IKAN TENGADAK ALBINO DAN HITAM (Barbonymus schwanenfeldii) DALAM KOLAM [Growth performance of the albino and black tinfoil barb (Barbonymus schwanenfeldii) in pond] - Gleni Hasan Huwoyon; Irin Iriana Kusmini (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2010)
Tinfoil barb is endemic species from West Kalimantan. Generally, the color has pleiotropic effect on the growth performance. The objective of study was to analyze the growth performance of albino and black tinfoil barb under communal rearing in concrete ponds. This study was using 3-5 g in weight and density was 20 fish per net (10 albinos and 10 black tinfoil barbs) with 4 replications. During rearing period, fish was fed with commercial pellet 5% body weight a day. The observation was done every 30 days up to 10 months. Growth was observed by weighting 10 fish per each color phenotypes. The results showed that albino tinfoil barb had better performance than black tinfoil barb in absolute length (albino: 7.2±0.52; black: 5.7±0.50), absolute growth (albino: 66.9±9.11; black: 46.3±8.39) and specific growth rate (albino: 0.94±0.047; black: 0.83±0.059).